2023
DOI: 10.25217/0020236369700
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Reliability and Validity of a Malaysian Version of Rathus Assertiveness Schedule as Drug Prevention Scale

Ahmad Jazimin Jusoh,
Muh Khairul Wajedi Imami,
Ciptro Handrianto
et al.

Abstract: The aim of this research was to verify the Malaysian version of Rathus assertiveness as a drug prevention scale in secondary students. The current research articipants were 211 secondary students in Johor, Selangor, and Kuala Lumpur, Malaysia. An exploratory factor analysis with principal axis factoring and varimax rotation was performed for the initial analysis. After the eigenvalue emerged, the data was suppressed to .30 to display the factor loading. The value of commonalities and factor loading was conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Suseelan et al (2022) investigated the mistakes made by low-ability students in solving word problems. The results of the investigation revealed that students' procedural skills need to be improved (Jusoh et al, 2023;Indrianto et al, 2024). (Claudia et al, 2021;Ukobizaba et al, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…Suseelan et al (2022) investigated the mistakes made by low-ability students in solving word problems. The results of the investigation revealed that students' procedural skills need to be improved (Jusoh et al, 2023;Indrianto et al, 2024). (Claudia et al, 2021;Ukobizaba et al, 2021).…”
Section: Introductionmentioning
confidence: 95%